Analisis Sensitivitas Sebagai Faktor Penting Dalam Suatu Pengambilan Keputusan Investasi - Hidayat, Lukman; Puspitasari, Ratih; Tantina, Tantina (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2011)
The objective of this research is to find out the feasibility of electric capacity changes expansion project from 400 MW to 520 MW at PT. Krakatau Daya Listrik, at the same time to bring about sensitiveness on four main elements at this project, that is selling, producing cost, variable cost, and investment. Itâs expected from the sensitiveness analysis, the Management can revaluate cash flow estimation of the project arranged to find out how far the sensitiveness degree of cash flow to various changes of independent variable respectively will be. If a certain variable mentioned above? The researchâs result shows that expansion project at PT. Krakatau Daya Listrik can be said feasible to be carried out. The consideration to decision of project feasibility can be looked at the feasibility criterion yielded, that is Net Present Value yields US.41.397.551,- Internal Rate of Return is 6,82%, higher than PT. KDLâs rate as high as 3,05%. Payback period is 7,8 years, shorter than credit term plan of the company, that is 10 years. The evaluationâs result shows that the most sensitive in expansion project is selling element. It has been proven by the author by performing sensitiveness analysis graph of changes on four elements above. The steepest element change is the most sensitive element. Because of selling is the most sensitive element, itâs the duty of PT. KDL Management to supervise either the realization of the project or its selling price if CCPP 120 MW project will be put in operation. This one must be taken notice because just by selling decreas of 5% the project wonât have feasibility to be carried out.